Can rivaroxaban be a drug of choice for treating heparin-induced thrombocytopenia in a patient with pulmonary thromboembolism? - Vavlukis, Marija; Kotlar, Irina; Taravari, Hajber; Poposka, Lidija; Kedev, Sasko (My University, 2017)
Heparin-induced thrombocytopenia (HIT) is an adverse effect of heparin therapy (1). There are two types of HIT: non-immunomediated (HIT-I) and immunomediated (HIT-II) disorders. HIT-II is characterized by the formation of IgG antibodies against the heparin-PLT factor 4 complex (PF4) (1, 2). Bounded with heparin, this factor creates a neoantigen and stimulates the production of antibodies (2). Activated PLTs, along with the heparin/PF4 antibody complex attached to their surface, undergo aggregation and premature removal from the circulation, leading to thrombocytopenia and additionally to a procoagulant state with high potential for thrombus formation and thromboembolic events (3). The incidence of HIT-II is 0.1%–1% in low-molecular-weight heparins (LMWH) and 3%–5% in un-fractionated heparin (UHF)- treated patients (3). In HIT-II, the PLT count drop can be seen 3–4 days after exposure in patients with pre-existing heparin- PF4 antibodies from a previous exposure to heparin, whereas in those exposed for the first time, the PLT count drops 5–10 days after heparin administration (3). It has been confirmed that new oral anticoagulants (NOACs) offer advantages regarding this side effect (4), and this case report aims to share our first positive experience in relation to the previously mentioned.
Keywords: heparin-induced thrombocytopenia; rivaroxaban; pulmonary thromboembolism